2003
DOI: 10.1189/jlb.0203068
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the c-ErbB-2/HER2 proto-oncogene in normal hematopoietic cells

Abstract: The HER2/c-ErbB-2 proto-oncogene is overexpressed in 25-30% of human breast cancers. We previously reported the c-ErbB-2 transcript in mononuclear cells (MNC) from bone marrow (BM), peripheral blood (PB), and mobilized PB (MPB). Here, we describe extensively the expression pattern of c-ErbB-2 mRNA and protein in normal adult hematopoietic tissue and cord blood (CB)-derived cells. Quantitative reverse transcriptase-polymerase chain reaction shows that the c-ErbB-2 transcript is expressed in hematopoietic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In this study, we examined NRG1-ErbB signaling in patients with schizophrenia using EBVtransformed B lymphoblasts because they are easily established from patients and can be maintained to investigate various cellular and molecular biological functions. Previous studies have confirmed the expression of ErbB receptors in primary hematopoietic cells, 46 B cell leukemia-derived lymphoblasts 47,48 and multiple myeloma cells, 49 suggesting that hematopoietic cells, especially the B-cell lineage, express ErbB receptors. Consistent with these previous findings, we found that ErbB2 and ErbB3 transcripts and proteins were expressed in all the EBV-transformed B lymphoblasts tested.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we examined NRG1-ErbB signaling in patients with schizophrenia using EBVtransformed B lymphoblasts because they are easily established from patients and can be maintained to investigate various cellular and molecular biological functions. Previous studies have confirmed the expression of ErbB receptors in primary hematopoietic cells, 46 B cell leukemia-derived lymphoblasts 47,48 and multiple myeloma cells, 49 suggesting that hematopoietic cells, especially the B-cell lineage, express ErbB receptors. Consistent with these previous findings, we found that ErbB2 and ErbB3 transcripts and proteins were expressed in all the EBV-transformed B lymphoblasts tested.…”
Section: Discussionmentioning
confidence: 74%
“…Figure 3C shows the ratio of circulating Neu-expressing cells relative to GAPDH in the blood at the time of sacrifice when the primary tumors in the WT/Neu and α 2 -null/Neu mice were of similar size; α 2 -null/Neu mice had a significantly larger proportion of these cells than WT/Neu mice (P = 0.005). Since c-ErbB2/Her2 is expressed in normal hematopoietic cells, the number of circulating tumor cells was also characterized by qRT-PCR for cytokeratin 19 (28). As shown in Supplemental Figure 3, increased numbers of circulating, cytokeratin 19-expressing cells were identified in the peripheral blood of tumor-bearing, α 2 -null/Neu in comparison with WT/Neu mice at the time of sacrifice.…”
Section: Loss Of the α 2 β 1 Integrin Increases Breast Cancer Metastamentioning
confidence: 99%
“…These proteins include epidermal growth factor receptors targeted in colon, lung, and head and neck cancers and the human epidermal growth factor receptor-2 (HER-2) in breast and other cancers (21). Of relevance, HER-2 has been detected in skin, breast, and placenta as well as in epithelial cells of the gastrointestinal, respiratory, reproductive, and urinary tracts (22) and has been detected on subsets of hematopoietic cells (23) and also functions in muscle (24).…”
Section: Opportunities and Challenges In Targeting Cdcp1 In Cancermentioning
confidence: 99%